Vitamin B6 levels do not correlate with severity of neuropathy in chronic idiopathic axonal polyneuropathy. Issue 1 (29th December 2021) - Stewart, Sarah L.; Thomas, Simone; Höke, Erol; Simpson, David; Singleton, J. Robinson; Höke, Ahmet
Abstract: Pyridoxine (vitamin B6) toxicity is known to cause a length‐dependent, sensory predominant axonal polyneuropathy. There is debate regarding the threshold at which intake levels can cause neurological symptoms through pyridoxine toxicity. We asked if elevated plasma vitamin B6 levels were related to outcome measures in a well‐characterized cohort of patients with chronic idiopathic axonal polyneuropathy (CIAP). We included 261 patients enrolled in the Peripheral Neuropathy Research Registry who had a complete dataset including a plasma vitamin B6 value. Patients with vitamin B6 deficiency (0‐4.9 μg/L) were excluded. We performed a chi‐square test for independence and analyzed the logistic relation of elevated plasma B6 level to nerve conduction studies (NCS), neurological examination findings, and patient‐reported symptoms controlling for age and time elapsed since neuropathy symptom onset. Plasma B6 level was not related to neuropathy severity. There was no logistic relation of elevated plasma B6 level to NCS results, examination features including toe strength, vibration sense, and deep tendon reflexes, or patient‐reported numbness or pain intensity. This study suggests that moderately elevated plasma B6 levels, even in the 100 to 200 μg/L range, are not associated with significantly worse neuropathy signs or symptoms. Although standard supplementation of B6 does not appear to have a major negative affect on CIAP, this study does not directly answer whether stopping supplementation will have a beneficial effect. Very few patients in the study had vitamin B6 levels >300 μg/L, suggesting that screening for vitamin B6 toxicity may be left to the discretion of the physician.